(untitled) (Research, Society and Development, 2020)
This work aims to report a case of autogenous bone grafting whose donor bed was a mandibular torus, for reconstruction of the atrophic area in the mandible, aiming at increasing the bone thickness available for installing a dental implant. A normossystemic 50-year-old male patient searched for dental services complaining about his smile. On the clinical examination, the patient presented bilateral mandibular torus and atrophic area in the left lower premolar region. A reconstruction procedure through the autogenous graft with right mandibular torus donor area, dental implant installation and implant-supported prosthetic rehabilitation were performed. It was proved that the mandibular torus is an efficient alternative of autogenous bone graft, which provides a sufficient volume gain for the implantation of the dental implant. The surgical technique used has proven to be safe and effective, however, it is important that the professional dentist is trained to perform it.